2011
DOI: 10.1152/japplphysiol.00069.2011
|View full text |Cite
|
Sign up to set email alerts
|

Lower vascular tone and larger plasma volume in Parkinson's disease with orthostatic hypotension

Abstract: Here, we test the role of two other possible factors: 1) a reduced peripheral vasoconstriction (which may contribute because PD includes a generalized sympathetic denervation); and 2) an inadequate plasma volume (which may explain why plasma volume expansion can manage orthostatic hypotension in PD). We included 11 PD patients with orthostatic hypotension (PD ϩ OH), 14 PD patients without orthostatic hypotension (PD Ϫ OH), and 15 agematched healthy controls. Leg blood flow was examined using duplex ultrasound … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
19
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(20 citation statements)
references
References 44 publications
(60 reference statements)
0
19
1
Order By: Relevance
“…With respect to the first possibility, Andersen et al found that, in PD patients without symptoms or signs of autonomic dysfunction, local reflexes did not differ from those +3 +5 +7 +9 +11 +13 +15 +17 +19 +21 +23 +25 +27 +29 75 50 150 B 120 100 80 60 125 100 mmHg bpm MSR -9 -7 -5 -3 -1 +1 +3 +5 +7 +9 +11 +13 +15 +17 +19 +21 +23 +25 +27 +3 +5 +7 +9 +11 +13 +15 +17 +19 +21 +23 +25 +27 +29 60 80 100 120 PD -TOH YHC . This finding was corroborated by Fusina et al 23 and more recently by Groothuis et al 8 Regarding the second possibility, it is noteworthy that baroreflex function assessment has concentrated on baroreceptor-HR reflex, even though PVR control is of greater importance during orthostatic stress. In the same manner, this attention has focused on the sensitivity of the baroreflex response and not in its latency.…”
Section: Discussionmentioning
confidence: 59%
See 4 more Smart Citations
“…With respect to the first possibility, Andersen et al found that, in PD patients without symptoms or signs of autonomic dysfunction, local reflexes did not differ from those +3 +5 +7 +9 +11 +13 +15 +17 +19 +21 +23 +25 +27 +29 75 50 150 B 120 100 80 60 125 100 mmHg bpm MSR -9 -7 -5 -3 -1 +1 +3 +5 +7 +9 +11 +13 +15 +17 +19 +21 +23 +25 +27 +3 +5 +7 +9 +11 +13 +15 +17 +19 +21 +23 +25 +27 +29 60 80 100 120 PD -TOH YHC . This finding was corroborated by Fusina et al 23 and more recently by Groothuis et al 8 Regarding the second possibility, it is noteworthy that baroreflex function assessment has concentrated on baroreceptor-HR reflex, even though PVR control is of greater importance during orthostatic stress. In the same manner, this attention has focused on the sensitivity of the baroreflex response and not in its latency.…”
Section: Discussionmentioning
confidence: 59%
“…Peripheral sympathetic vasoconstriction, in part baroreflex-mediated, is responsible for the rebound of BP from SBP b to SBP os following AS 1,18 . Local reflexes are involved as well in this PVR increment 8,19,20 . Except for the venoarteriolar response (VAR) in those aged over 75 years, both central and local responses are independent of age in healthy subjects 1,19,21 .…”
Section: Discussionmentioning
confidence: 97%
See 3 more Smart Citations